Transformasi Perpustakaan Berbasis Inklusi Sosial (TPBIS) Berdasarkan Perspektif Pendidikan Moderasi Beragama Muhammadiyah Menurut Pemikiran K.H. Ahmad Dahlan - Yuliasih, Yuyu; Rachmatullah, Richard (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
This study aimed to determine the Program Library Transformation Base On Social Inclusion (LTBSI) Base On Perspective Education Religious Moderation Muhammadiyah According To Throught K.H. Ahmad Dahlan. In improving students abilities, between programs LTBSI with Perspective Education Religious Moderation Muhammadiyah According To Throught K.H. Ahmad Dahlan, have something in common, namely both inclusive and moderate without distinguishing background as gender, physical appearance, racial, ethnic, religion, social status, and economics as both emphasizing the existence of bias towards marginalized communities. Data analyzed in this study using the literature review method, data sources in the form of book, relate journal, as well as article wich is published national journal, show that the Program LTBSI is a program National Library of the Republic of Indonesia who has a very appropriate perspective and inspired by the pillars Base On Perspective Education Religious Moderation Muhammadiyah According To Throught K.H. Ahmad Dahlan, namely (1) there is an attitude national commitment, (2) there is an attitude tolerance, (3) there is an attitude not extreme (not-violence), and (4) there is an attitude accommodating to local culture values. The program LTBSI, in improving the welfare of marginalized communities by the National Library of the Republic of Indonesia, attitude has been adopted “wasathiyah” “middle way”, with principles tawassuth (not extreme), moderat (moderation, middle way, balance, justice), dan tasamuh (there is an attitude tolerance, relieve, mutual respect), and this fits perfectly and according to condition plural nation like in Indonesia. Abstrak Penelitian ini bertujuan untuk mengetahui Program Transformasi Perpustakaan Berbasis Inklusi Sosial (TPBIS) Berdasarkan Perspektif Pendidikan Moderasi Beragama Muhammadiyah Menurut Pemikiran K.H. Ahmad Dahlan. Dalam meningkatkan kemampuan peserta didik, antara Program TPBIS dengan perspektif pendidikan moderasi beragama Muhammadiyah menurut pemikiran K.H. Ahmad Dahlan, memiliki kesamaan yaitu sama-sama bersifat inklusif dan moderat tanpa membeda-bedakan latar belakangnya, seperti gender, kondisi fisik, ras, etnis, agama, status sosial, dan ekonomi serta sama-sama menekankan adanya keberpihakan terhadap masyarakat yang termarginalkan. Data yang dianalisis dalam penelitian ini dengan metode kajian pustaka, dari sumber data berupa buku-buku, jurnal- jurnal yang berkaitan, maupun artikel-artikel yang terbit di jurnal nasional, menunjukkan bahwa program TPBIS merupakan program Perpusnas RI yang memiliki perspektif yang sangat sesuai serta dijiwai oleh pilar-pilar pendidikan moderasi beragama Muhammadiyah menurut pemikiran K.H. Ahmad Dahlan, yaitu (1) adanya sikap komitmen kebangsaan, (2) adanya sikap toleransi, (3) adanya sikap anti kekerasan, serta (4) adanya sikap akomodatif terhadap nilai-nilai budaya lokal. Pada program TPBIS tersebut, dalam meningkatkan kesejahteraan masyarakat yang termarginalkan oleh Perpustakaan Nasional Republik Indonesia, telah diterapkan sikap “wasathiyah” “jalan tengah” dengan prinsip-prinsip tawassuth (tidak ekstrem), moderat (cenderung ke arah jalan tengah, berkeseimbangan, berkeadilan), dan tasamuh (sikap toleransi, tenggang rasa, lapang dada, saling menghormati), dan ini sangat cocok dan sesuai dengan kondisi Bangsa Indonesia yang plural.